68 Injury related death of production worker in Shenzhen from 2007–2011. (11th October 2013) - Liu, X J; Wu; Fu; Wang; Cheng
Abstract : Objectives: There are many production workers in Shenzhen, a city of immigrants, which is a public problem, should be concerned. This study aimed to explore the nature of injury related death of production worker, and provided basic interventional measures. Methods: The data were collected from the Death Surveillance System in China from 2007 Jun 1 st to 2011 Dec 31 st . The cause of injury related death was coded from V01 to Y98, and the occupation was production worker. The data were analysed by SPSS 15.0. Results: 517 deaths of production worker due to injury were indentified from 2007–2011 in Shenzhen. There were 437 male workers (84.5%), and 80 female workers (15.5%). The average age was 34.72. The first five cause of injury death was W17, V03, V09, W20, and V02 (ICD-10, fall and traffic injury), accounted for 15.7%, 11.6%, 10.6%, 7.9% and 3.9%, respectively. The distribution of injury cause in different district was significant different (p<0.05). Conclusions: Production worker is a dangerous job. More effective measures should be taken to prevent fall and traffic injury for production worker. The aim population is the young male worker in special district.